Upaya Peningkatan Pengetahuan Keluarga Untuk Mencegah Risiko Hiperglikemia Pada Tn.S Di Desa Gatak - Trianawati, Luthfi, Abi Muchlisin, S.KM., M.Kep, Supratman, Ph.D (2017)
Diabetes mellitus is a metabolic disorder that is characterized by hyperglicemia related to carbohydrate metabolism abnormality in fat and proteins caused by decreased insulin secretion/decrease insulin sensitivity/both and cause complications of neuropathy and makrovaskular mikrovaskular. This research method using nursing approach includes studies on nursing diagnosis planning implementation and evaluation . The library collects study references related to the case which was appointed as the title. While the method of data collection by means of interviews and observations physical examination. Nursing diagnoses made after the assesment is done, the planning and execution carried out in accordance with healt problems and evaluation conducted on the last day. The results showed there was a significant relationship between knowwledge with the handling to prevent hyperglicemia in diabetics mellitus. From knowledge then will develop an awareness of the family how dangerous the disease diabetes mellitus family able to care for and then take the right decision. Changes in the pattern of life is a difficult thing done but nothing is impossible because anything can be changed while there is ability and effort. Knowledge of the family is one of the keys to change the pattern of life is wrong. Awarenes for change would occur over his running time.